Relationship between recurrently elevated hsCRP and adverse cardiovascular events among depressed patients in China: a time-to-event analysis - Wu, Ying; Mi, Yuwei; Cui, Hanbin; Song, Qifa; Ruan, Liemin (Frontiers in Cardiovascular Medicine, 2025)
ContextPersistent inflammation has been considered a biological link between depression and cardiovascular diseases(CVDs). Multipoint assessments of inflammation provide a more reasonable understanding of an individual's inflammatory status compared to single-point measurements. However, few studies have established strategies to investigate multipoint measurements of plasma high-sensitivity C-reactive protein(hsCRP).Aims/Objective/HypothesisTo elucidate the association between recurrent elevations in hsCRP and cardiovascular events among depressed patients.MethodsThis retrospective cohort study analyzed medical records over a ten-year follow-up to evaluate the association between longitudinal hsCRP patterns and recurrent cardiovascular events in patients with depression. An age-adjusted gamma frailty time-to-event model was used to assess the risk for three primary outcomes: chronic ischemic heart disease (CIHD), atrial fibrillation (AF) and other arrhythmias, and major adverse cardiac events (MACE). The cumulative incidence of these recurrent events was estimated using the Mean Cumulative Function (MCF).ResultsThe study included 10,770 patients [7,428 (68.97%) females]. Patients were classified into five groups based on hsCRP levels: hsCRP < 3 mg/L (n = 4,209, 39.08%), 3–8 mg/L (n = 1,697, 15.76%), one measurement of hsCRP ≥ 8 mg/L (n = 3,007, 27.92%), two to three measurements of hsCRP ≥ 8 mg/L (n = 1,349, 12.53%), and >3 measurements of hsCRP ≥ 8 mg/L (n = 508, 4.72%). The MCFs for CIHD across the five groups were 1.156, 1.339, 1.417, 2.021, and 2.36, respectively. For AF and other arrhythmias, the corresponding MCFs were 0.796, 1.369, 1.008, 0.858, and 1.578, while for MACE, they were 0.084, 0.089, 0.134, 0.196, and 0.172. Compared with the reference group (hsCRP < 3 mg/L), the adjusted hazard ratios (HRs) for CIHD were 1.28 (P = 0.14), 1.19 (P = 0.17), 1.70 (P < 0.001), and 1.88 (P < 0.001) across the other four groups; for AF and other arrhythmias, they were 1.38 (P = 0.07), 1.00 (P = 0.99), 1.04 (P = 0.84), and 1.83 (P < 0.01); and for MACE, they were 0.85 (P = 0.65), 0.73 (P = 0.24), 1.21 (P = 0.49), and 1.28 (P = 0.40), respectively.ConclusionsThe gamma frailty time-to-event model indicated a link between persistent inflammation and cardiac events. Recurrent hsCRP elevations were more strongly associated with cardiovascular events than those observed in cross-sectional analyses. Trial RegistrationNCT06239246; ChiCTR2400089334.